Islam and leadership universal values in the construction of a pluralistic world - Ahmad H.Osman, Rahmah (2017)
Leadership can be defined as “a dynamic relationship based on mutual influence and common purpose between leaders and collaborators in which both are moved to higher levels of motivation and moral development as they affect real, intended change.” (Rost, 1991). At the same time, Burns [1978] defines leadership as “leaders inducing followers to act for certain goals that represent the values and the motivations — the wants and needs, the aspirations and expectations — of both leaders and followers.” The transformational dimension highlighted by both definitions is very much a part of the Islamic paradigm of leadership, which stresses the reciprocal enrichment of the leaders and the followers. “Everything rises and falls on leadership.” This is a quote made famous by Dr. John C. Maxwell, in his bestselling book, The 21 Irrefutable Laws of Leadership. When leadership is great, success inevitably follows. Likewise, when leadership is poor, failure inevitably follows. This keynote address elaborates on a number of leadership skills and styles proposed by a number of renowned leadership trainers and laments on the incredible leadership skills and characteristics of our Prophet , which he exemplified in all areas of his life, in a plurastic world.